2013
DOI: 10.1016/j.cplett.2013.03.035
|View full text |Cite
|
Sign up to set email alerts
|

How do proteins locate specific targets in DNA?

Abstract: Many aspects of biology depend on the ability of DNA-binding proteins to locate specific binding sites within the genome. Interest in this target search problem has been reinvigorated through the recent development of microscopy-based technologies capable of tracking individual proteins in real-time as they search for binding sites. In this review we discuss how two different proteins, lac repressor and RNA polymerase, have solved the target search problem through seemingly different mechanisms, with an emphas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 88 publications
0
47
0
Order By: Relevance
“…S2) suggests that the off-rate of Fis (and potentially other nucleoid proteins) might be accelerated in vivo beyond the level due to Fis-Fis exchange alone. The abundant nucleoid proteins, whose cellular levels vary with growth conditions (19), may therefore strongly influence dynamics of protein-DNA interactions on chromosomes, including protein-DNA search rates (1,33,34). Shifts in nucleoid protein concentration could provide a general mechanism to trigger rapid rearrangement of transcription factors and therefore reprogramming of transcriptional regulation.…”
Section: Facilitated Dissociation In Vitro Ex Vivo and In Vivomentioning
confidence: 99%
“…S2) suggests that the off-rate of Fis (and potentially other nucleoid proteins) might be accelerated in vivo beyond the level due to Fis-Fis exchange alone. The abundant nucleoid proteins, whose cellular levels vary with growth conditions (19), may therefore strongly influence dynamics of protein-DNA interactions on chromosomes, including protein-DNA search rates (1,33,34). Shifts in nucleoid protein concentration could provide a general mechanism to trigger rapid rearrangement of transcription factors and therefore reprogramming of transcriptional regulation.…”
Section: Facilitated Dissociation In Vitro Ex Vivo and In Vivomentioning
confidence: 99%
“…The nature of diffusive transport of DNA binding proteins in the context of target search has been of intense interest for decades and has extensive implications in many different facets of essential cellular processes, ranging from DNA replication and gene regulation to maintenance of genome stability (Kad et al, 2010; Lee et al, 2014a; Redding and Greene, 2013; Tafvizi et al, 2011b). The importance of search dimensionality was first pointed out by Adam and Delbruck, who suggested that the search process can be accelerated by collapsing a three-dimensional search into a one-dimensional search along the DNA (Adam and Delbrück, 1968).…”
Section: The Target Search Problem: Solving the Speed-stability Pamentioning
confidence: 99%
“…Similarly, 55% of MutLα found mismatch-bound MutSα through pathway involving a 1D search, whereas the remaining 45% used a 3D association pathway. This ability to engage lesions through either 1D or 3D pathways is not surprising or even unexpected; moreover it is crucial to recognize that the ratio of 1D to 3D binding events is expected to change as a function of protein concentration [37, 38]. The fraction of proteins utilizing a 1D search will always increase at low protein concentrations, whereas the fraction of those that bind through a 3D pathway will always increase at higher protein concentrations [37, 38].…”
Section: Mmr Proteins As Models For Studying Diffusive Motion On Dnamentioning
confidence: 99%
“…This ability to engage lesions through either 1D or 3D pathways is not surprising or even unexpected; moreover it is crucial to recognize that the ratio of 1D to 3D binding events is expected to change as a function of protein concentration [37, 38]. The fraction of proteins utilizing a 1D search will always increase at low protein concentrations, whereas the fraction of those that bind through a 3D pathway will always increase at higher protein concentrations [37, 38]. This concentration-dependent effect on target searches needs to be considered when trying to interpret how results obtained from a single-molecule measurement of 1D diffusion might pertain to in vivo scenarios where the protein concentrations (among other things; see below) might differ substantially from in vitro conditions.…”
Section: Mmr Proteins As Models For Studying Diffusive Motion On Dnamentioning
confidence: 99%
See 1 more Smart Citation